Upaya Guru Mengatasi Kesulitan Membaca pada Peserta Didik Kelas 1 di SD Negeri 1 Wajak Lor Tulungagung - Maghfira Raudya Tuzahra; Yasip Yasip (Jurnal Simki Postgraduate, 2024)
Basic education is the main foundation in forming children's character and academic abilities. One of the fundamental skills that students in the early grades must master is the ability to read. This ability is not only the basis for understanding other subject matter, but is also important in everyday life. Therefore, it is important for teachers at the elementary school level to ensure that every student has good reading skills from an early age. This research aims to explore and analyze the efforts made by teachers to overcome reading difficulties in students. The research method used is a qualitative research method and a type of field research. The results of the research show that the teacher uses letter cards in the learning method, so it is more effective in helping students develop their reading skills. By using this method learning becomes more fun and interactive and helps students remember the shapes and sounds of letters. Then provide private tutoring for students who have difficulty reading, this is done during break times.